Español - Franco, Joaquín (2020)
In Yucatan it is produced between ten thousand and fifteen thousand tons of honey per year; more thaneleven thousand Mayan-speaking beekeepers in rural areas depend on the economic flow from thisincome. However, due the absence of an organized incentive program for apiculture, there is no synergybetween the components of this system. This results in a weak system unable to face latent externalthreats that could cause the extinction of bees, jeopardizing other income-producing activities such asagriculture, cattle industry and forestry. In this article, presented at the 6th International SustainabilityCongress 2019, in México, is shown qualitative research on the emerging existence of ApiculturalProduct System in two regions of Yucatan. The main objective is to analyze the current situation ofbeekeeping in two municipalities of Yucatan, belonging to the western and northwestern region, thekey actors that are members of this system, analyzing their level of preparation and capacity to fightexternal threats to Yucatecan beekeeping. Preliminary results obtained through the documentaryreview shows a lack of policies aimed at strengthening agro-ecological over conventional crops andabsences of strategic alliances.